2017
DOI: 10.1186/s12866-017-0986-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification and analysis of genomic islands in Burkholderia cenocepacia AU 1054 with emphasis on pathogenicity islands

Abstract: BackgroundGenomic islands (GIs) are genomic regions that reveal evidence of horizontal DNA transfer. They can code for many functions and may augment a bacterium’s adaptation to its host or environment. GIs have been identified in strain J2315 of Burkholderia cenocepacia, whereas in strain AU 1054 there has been no published works on such regions according to our text mining and keyword search in Medline.ResultsIn this study, we identified 21 GIs in AU 1054 by combining two computational tools. Feature analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…The presence of Putative GIs was also predicted using IslandViewer 4 ( Bertelli et al, 2017 ), unique GIs were manually confirmed and curated in the genome sequences of B. cenocepacia IST439 and B. multivorans IST419. For this confirmation, it was considered that they are unique continuous DNA regions absent in the available genome sequences of the published epidemic clones and longer than 10 kbp, flanked, at both sides, by homologous regions (especially those inserted immediately downstream of tRNA), and have lower (or higher) GC content compared with the rest of the genome ( Guo et al, 2017 ; Nunvar et al, 2017 ). The absence of DNA regions homologous to these unique GIs in the genomes of epidemic clones – B. cenocepacia ET12 and ST32 ( Holden et al, 2009 ; Nunvar et al, 2017 ) and B. multivorans ATCC_17616 and ATCC_BAA-247 ( Komatsu et al, 2003 ; Johnson et al, 2015 ; Johnson et al, 2016 ) – was confirmed and visualized by Progressive MAUVE whole genome pairwise alignment and ACT/Artemis ( Carver et al, 2005 ; Darling et al, 2010 ).…”
Section: Methodsmentioning
confidence: 99%
“…The presence of Putative GIs was also predicted using IslandViewer 4 ( Bertelli et al, 2017 ), unique GIs were manually confirmed and curated in the genome sequences of B. cenocepacia IST439 and B. multivorans IST419. For this confirmation, it was considered that they are unique continuous DNA regions absent in the available genome sequences of the published epidemic clones and longer than 10 kbp, flanked, at both sides, by homologous regions (especially those inserted immediately downstream of tRNA), and have lower (or higher) GC content compared with the rest of the genome ( Guo et al, 2017 ; Nunvar et al, 2017 ). The absence of DNA regions homologous to these unique GIs in the genomes of epidemic clones – B. cenocepacia ET12 and ST32 ( Holden et al, 2009 ; Nunvar et al, 2017 ) and B. multivorans ATCC_17616 and ATCC_BAA-247 ( Komatsu et al, 2003 ; Johnson et al, 2015 ; Johnson et al, 2016 ) – was confirmed and visualized by Progressive MAUVE whole genome pairwise alignment and ACT/Artemis ( Carver et al, 2005 ; Darling et al, 2010 ).…”
Section: Methodsmentioning
confidence: 99%
“…3 and 5). Specifically, BCC08 and BCC05 should represent B. cenocepacia genomovars IIIA and IIIB, respectively [23,56,57]. The dDDH and Fig.…”
Section: Reclassification Of the Bcc Based On Species Tree And Dddh/animentioning
confidence: 99%
“…are opportunistic bacteria and include the human pathogens Burkholderia cepacia (causing pulmonary infections) and Burkholderia pseudomallei (causing melioidosis). Intriguingly, both genera make use of genomic islands for pathogenicity (67), are susceptible to the same phage-transfer mechanisms (68), and are each capable of influencing gene expression in the other (69,70). Moreover, Burkholderia spp.…”
Section: Discussionmentioning
confidence: 99%